How to Listen to Pachamama’s Testimonio: Lessons from Indigenous Voices - Luis I Prádanos; Leonardo Esteban Figueroa Helland (Studies in 20th & 21st Century Literature, 2015)
This article analyzes the collective, open-access, and modifiable publication El Vivir Bien como respuesta a la Crisis Global as a posthumanist testimonio or ecotestimonio intending to give voice to the biotic community of the Andes. Written by Quechua and Aymara people and presented to the United Nations by the Plurinational State of Bolivia, this document targets the global ecological, financial, and social crises from the perspective of Indigenous knowledges. This document also exemplifies the worldwide reemergence of Indigenous voices that are confronting the global ecological crisis and its environmental injustices through the revitalization of Indigenous worldviews and practices. This ecotestimonio conveys, among many timely lessons, the Indigenous teaching that humans must listen carefully to the non-human world to learn from Pachamama how to interrelate as humans and with non-humans to collaborate in ensuring the continuing vitality of the community of life. If we listen carefully to Pachamama’s testimony, as Indigenous voices urge, doubt must be cast upon the viability of ideas celebrated by hegemonic Western modern discourses like "development," "progress," or ‘"economic growth." Instead, these voices invite us to rethink the place, functions, and responsibilities of humans as members of the web of life.
Keywords: ecotestimonio; posthumanist testimonio; Buen Vivir; environmental justice; global socio-ecological crisis